Corporate governance: the inputs to outcomes evolution. Issue 2 (1st May 2020) - de Beer, Linda
Abstract : Purpose: The purpose of this study is to demonstrate that there was a clear shift from the First King Report in 1994, which advocated an input approach to corporate governance, to the Fourth King Report in 2016 that proposed an outcomes-based approach to corporate governance. It will be demonstrated that there was a gradual shift from an "apply-or-explain" approach in the earlier editions of the King Reports, to an "apply-an-explain" approach in the fourth edition of the King Report. Design/methodology/approach: Historical narrative and analysis. Findings: The fourth King Report, published in 2016, encapsulates an evolution in corporate governance thinking where four good governance outcomes – ethical culture, good performance, effective control and legitimacy – are placed at the forefront of measuring governance, with governance principles and practices following from these outcomes. Originality/value: This study is part of a special issue that looks at the contribution of the King Reports to governance globally.